Remittance Inflows and Economic Growth of Nepal: An Error Correction Approach (Economic Journal of Nepal, 2015)
The basic purpose of this paper is to examine the contribution of remittance on economic growth of Nepal including gross domestic product, foreign direct investment, export and import in current price. This study applies Ordinary least square method (OLS) on time series data from 1990/91 to 2013/14. The results have shown the fact that a positively significant impact of remittance on gross domestic product of a country (Model I). The coefficients of remittance, foreign direct investment and export positive signs. However, observed negative signs of import. Engle- Granger co integration test revealed long run relationship among the variable. Engle- Granger error correction test has been applied correcting the previous year disequilibrium by 1.8 percent annually. The null hypothesis are not serially correlated, residuals are homoscedasticity, residuals are normally distributed which is desirable for the Error Correction Model. So in conclusion this error correction model is accepted. Granger causality test finds there is no causality exist among the variables.